(untitled) (Revista Brasileira de Iniciação Científica, 2021)
This work aims to analyze the elements of the academic-scientific trajectory of the undergraduate student, based on the influence of economic and cultural capital in the socialization process and in the course of her studies. The survey had the participation of 156 volunteers enrolled in 36 undergraduate courses at a Brazilian federal institution. The analysis, based on Bourdieu, revealed that the social origin and cultural capital of students can have implications both for their insertion, as well as for the choices and permanence in higher education.